2017
DOI: 10.16955/bitkorb.340046
|View full text |Cite
|
Sign up to set email alerts
|

Çanakkale ili börülce üretim alanlarında Hıyar mozaik virüsü (Cucumber mosaic virus; CMV)’nün tespiti ve kılıf protein genine göre moleküler karakterizasyonu

Abstract: In 2015-2016, surveys were carried out in areas of Çanakkale province where cowpea and bean were cultivated. Twenty-two samples (14 bean and 8 cowpea) showing virus and virus-like symptoms were collected from these areas. The collected samples were tested by DAS-ELISA to determine the presence of Cucumber mosaic virus (CMV) infection and 6 samples out of 22 were found to be infected with CMV. While the determined all CMV infection was found in cowpea samples, there was no infection found in bean samples. Coat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…Based on previous studies carried out in Turkey, CMV SI-A has been found in pepper, tomato and watermelon (Caglar, 2006), CMV SI and SII in pepper, tomato, cucumber, watermelon and melon (Sarı, 2015), CMV SI-B in cowpea (Karanfil and Korkmaz, 2017) and, CMV SI-A in spinach (Kurtoglu and Korkmaz, 2018). Even though CMV has been detected on a wide range of hosts in Turkey, subgroup categories and their classification of most of them were not currently completed at the nucleotide levels.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on previous studies carried out in Turkey, CMV SI-A has been found in pepper, tomato and watermelon (Caglar, 2006), CMV SI and SII in pepper, tomato, cucumber, watermelon and melon (Sarı, 2015), CMV SI-B in cowpea (Karanfil and Korkmaz, 2017) and, CMV SI-A in spinach (Kurtoglu and Korkmaz, 2018). Even though CMV has been detected on a wide range of hosts in Turkey, subgroup categories and their classification of most of them were not currently completed at the nucleotide levels.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of CMV in tobacco has been reported by several researchers as both natural hosts (Chatzivassiliou et al, 2004;Dai et al, 2012;Zhang et al, 2013) and experimental host (Tian et al, 2009;Chikh Ali et al, 2012). It has a nationwide host range with the exception of tobacco, which includes: Myrtle leaf milkwort, globe artichoke, parsley, mint, broccoli, squash, olives, cabbage, peppers, lettuce, spinach, cowpea, gladiolus, tomatoes, zucchini, cucumber, ornamental plants (daffodils, hyacinths, lilies), bean and spinach (Gümüs et al, 2004;Beler and Acıkgöz, 2005;Sevik and Akcura, 2011;Culal Kılıc and Yardımcı, 2012;Erkan et al, 2013;Ergün et al, 2013;Culal Kılıc et al, 2015;Uzunoğulları and Gümüs, 2015;Sertkaya, 2015;Karanfil et al, 2016;Gökdag et al, 2016;Güngör et al, 2017;Karanfil and Korkmaz, 2017;Koc and Fidan, 2017;Sevik, 2012Sevik, , 2017. Since its transmission to tobacco is not seed-borne (De Bokx and Huttinga, 1981), its presence and prevalence can stem from other virus sources like weeds, the suitable climate environment for active aphid populations throughout tobacco production season and acquired from other cultivated plants grown from CMV-infected seeds (Kaplan et al, 1997;Tsitsipis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As myrtifolia, bean and spinach, pepper, tomato, cucumber, olive, and others (Beler and Açıkgöz, 2005;Çulal Kılıç and Yardımcı, 2012;Ergün et al, 2013;Erkan et al, 2013;Gökdağ et al, 2016;Güngör et al, 2017;Gümüş et al, 2004;Karanfil and Korkmaz, 2017;Karanfil et al, 2016;Sevik and Akcura, 2011;Sevik, 2012;Sertkaya, 2015, Uzunoğulları andGümüş, 2015). Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…TuMV, afit türleri tarafından kolayca taşınabilmektedir [13]. Ülkemizin birçok bölgesinde farklı illerde lahanagil bitkilerinde TuMV tespit edilmiş ve populasyon yapıları aydınlatılmıştır [14][15][16].…”
Section: Introductionunclassified
“…Ülkemizde kanola bitkilerinde virüs enfeksiyonu Trakya Bölgesi'nde yürütülen çalışmalar ile tespit edilmiştir. Bu çalışmalar ülkemizde kanola virüsleri ile ilgili yapılan ilk araştırmalardır [16]. Ancak Karadeniz Bölgesi'nde Samsun ilinde özellikle birçok lahanagil grubu bitki türlerinin yoğun olduğu ve kanola üretiminin yapıldığı önemli tarımsal potansiyele sahip bir bölgede, kanola hastalıklarına yönelik herhangi bir çalışma bulunmamaktadır.…”
Section: Introductionunclassified